A comparative study between E.Coli O157:H7 and Coliform bacteria isolated from locally soft cheese - Al-Jaleel, Raghad A. Abd (The Iraqi Journal of Veterinary Medicine, 2008)
The main objective of this study was to isolate, identify andenumerate the E.coli O157:H7 bacteria and coliform bacteria fromlocally manufactured soft cheese.A total of 50samples of local soft cheese were collected and examinedfrom local markets of (5) different areas of Baghdad city which was { Aldora,Al-Amria,Al-Kadmia,Al-Karada,Al-Kazalia} 10 samples for eacharea.The results showed that the highest average counts of E.coli O157:H7and coliform bacteria was in Al-Dora 73.63 × 105and 956 × 105cfu/mlwhile the lowest average counts in Al-Kazalia 3.12× 105and 43.7×105cfu/ml .The result of the statistical analysis showed that there were a significantdifferences (p<0.05) between E.coli O157:H7 and coliform bacteriabetween Al-Dora and the other areas in this study which was {Al-Kadmmea,Al-Karada,Al-Ammrea,Al-Kazalia} but there were nosignificant differences (p<0.05) between the tow kinds of bacteria ineach area.It was conducted that the higher average of pollution for locally softcheese with E.coli O157:H7 was in Al-Dora , the reason of this higherpollution may be due to un healthy condition during milk collection usedfor milk processing or during the processing itself